Average comfortable opening time of the mouth a pilot study - Arenas, Michelle
Providing satisfactory treatment with the least amount of risk and discomfort is the primary concern of dentists. Doing dental procedures mostly requires access to posterior teeth. Patients are asked to keep their mouths open for long appointments. Opening the mouth as wide as a person can for an extended period of time can result to fatigued muscles, torn ligaments, and dislocated, swollen and bruised temporomandibular joint. The aim of the study was to determine the average comfortable opening time of the mouth and to test the relationship of comfortable mouth opening time between gender and clinical procedures. A total of 45 subjects participated in the study. They were asked to inform the researchers if they felt pain or discomfort while their mouths were open during the clinical procedure. The results showed that the average comfortable mouth opening time of the participants is 188.71 seconds (3 minutes, 8 seconds). For those who underwent oral examination, their average time is significantly higher (218.38 seconds) than those who just opened their mouths (162.75 sec). Males (219.64 sec) generally have higher average time than females (150.05sec) and they are significantly different. However, the interactions of the independent variables showed no significant difference.